2014
DOI: 10.1002/qua.24794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bondons by Goldstone mechanism with chemical topological indices

Abstract: The Goldstone symmetry breaking algorithm is applied on ϕ2 and ϕ4 chemical field contributions weighted, respectively, by the sphericity and extreme‐sphericity topological indices to provide for stable chemical bonding in the high temperature regime, the typical mass for the bondon, and the associated quantum boson. The method is applied to a representative series of polycyclic aromatic hydrocarbons providing an aromaticity hierarchy comparable with the scale‐based on the chemical hardness; present calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, it has half-integer Hall conductance, which indicates promising applications in nanoelectronics. Graphene is also proposed to be a topological insulator (TI) with a band gap opening at the Dirac point by strain or functional group modification with spin-orbit coupling (SOC) [ 13 , 14 , 15 ]. However, the gap is too small to be detected, let alone having applications at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has half-integer Hall conductance, which indicates promising applications in nanoelectronics. Graphene is also proposed to be a topological insulator (TI) with a band gap opening at the Dirac point by strain or functional group modification with spin-orbit coupling (SOC) [ 13 , 14 , 15 ]. However, the gap is too small to be detected, let alone having applications at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Such intriguing topological phenomena may relate to the formation and propagation of the quasi-quantum bosonic particle called the bondon [24], carrying certain topological chemical bonding information along a chemical structure-with more thermochemical observable effects when it relates to extended graphenic systems [25,26]. Bondonic theory may also eventually explain the homologies of chemical structures, as proven by the aid of the symmetry breaking mechanism, thus balancing the fermionic vs. bosonic (in)formation with direct influence on the aromatic or reactivity degree of a certain compound [27].…”
Section: Results: Topological Similarities Between Toroidal and Klein Bottle Polyhexesmentioning
confidence: 99%
“…Later, a number of degree-based and degree sum-based descriptors, like the group of Zagreb, atomic bond connectivity, harmonic, and others, evolved, each displaying a distinct set of relationships [26]. A substantial amount of research into degree-based and degree sum-based topological descriptors has found correlations between these measures and a wide variety of physical and chemical properties, such as stability, boiling points, heat formation, band gaps, etc., of the investigated molecules and compounds [27][28][29].…”
Section: Introductionmentioning
confidence: 99%